Donkey milk composition and its therapeutic applications - BHARDWAJ, ANURADHA; PAL, YASH; LEGHA, RAM AVTAR; SHARMA, PARVATI; NAYAN, VARIJ; KUMAR, SANJAY; TRIPATHI, HEMA; TRIPATHI, B N (The Indian Journal of Animal Sciences, 2020)
Milk contains plentiful nutrients. In Western countries, cow’s milk fat is supposed as a risk factor for health because it is a source of a high fraction of saturated fatty acids. There has been increasing attention in donkey’s milk. Donkeys’ milk is preferential as a potential new dietetic food and a good alternative for infant nutrition in the case of bovine milk protein allergy. The microbiota present in this food may be responsible for its beneficial effects. Considering the potential health benefits, an increase in utilization of donkeys’ milk is expected. The present review addresses various aspects of donkey milk with special emphasis on milk yield, composition, shelf life, antimicrobial, therapeutic and cosmetic properties.